THE EFFECT OF LETTER CARD MEDIA ON LEARNING OUTCOMES IN ELEMENTARY LEARNING - Minar Trisnawati Tobing; Eva Pasaribu; Nancy Purba (SENSEI RESEARCH CENTER, 2023)
This study aims to determine the effect of Letter Card Media on the Theme of Living in Harmony and the Sub-themes of Living in Harmony at Home to Improve Student Learning Outcomes in Class II SD Negeri 095191 Lihas. The research design used was a quantitative approach with an experimental method in the form of a one group pretest posttest design without any comparison group. The population in this study were all second grade students at SD Negeri 095191 Lihas and the sample used was 30 students at SD Negeri 095191 Lihas. The sample technique used is random sampling with two research variables, namely the dependent variable in the form of student learning outcomes, and the independent variable in the form of letter card media. The data collection technique is the test technique. The results of testing the hypothesis using the t test technique paired sample t test with the help of the SPSS Version 21 program, based on the calculation results that the significant value is 0.000 <0.05, so that ho is rejected and ha is accepted or by slamming tcount > ttable with df = (n- 1) namely tcount = 14.68 > ttable = 2.04. So it can be concluded that there is an effect of using letter card media on the theme of living in harmony, sub-theme of living in harmony at home, to improve student learning outcomes in class II SD Negeri 095191 Lihas